Body image perception, dietary practices and physical activity of overweight and normal weight Malaysian female adolescents - Pon, Lai Wan; Kandiah, Mirnalini; Mohd Taib, Mohd Nasir (Nutrition Society of Malaysia, 2004)
Body image plays an important role in the management of body weight, especially among female adolescents. This study examined the differences in body image perception, weight management knowledge, eating behaviour and physical activity between overweight and normal weight Malaysian female adolescents. Body mass index screening was done on 588 secondary school students to identify overweight (OW) and normal weight (NW) subjects. A BMI-for-age of => 85th percentile and between => 5th and < 85th percentile were used as cut-offs for identifying suitable subjects of overweight and normal weight, respectively. Fifty girls identified as being OW were matched for age and ethnicity with 50 NW students. Subjects completed a self-administered questionnaire on demographics, eating behaviour and physical activity, a weight management knowledge inventory (WMKI) and the Body Silhouette Chart. The study sample comprised Malays (40%), Chinese (30%) and Indians (30%) with a mean age of 14.76 ± 1.15 years. The majority of them were from families with a monthly household income of less than RM1,000. Significantly more NW subjects (χ2=6.112, p=0.013) than OW subjects had incorrect perception of their current body weight status. The WMKI revealed that more OW subjects (64%) than NW subjects (52%) had a low level of weight management knowledge. Eating behaviour patterns were not significantly different between OW and NW subjects, but more OW subjects skipped one or more daily meals as compared to their NW counterparts (χ2=0.174, p=0.010). Physical activity patterns were similar in both groups. Healthy eating and physical activity promotion programmes in schools should include sound weight management practices.